Algunas reflexiones sobre la problemática en la ejecución de proyectos hidroenergéticos en el marco de la normativa vigente en materia de recursos hídricos - Lock Benavides, Sandra (2019)
When the law and the competent authorities contradict each other, the execution of projects is discouraged, among the growing legal uncertainty, which occurs with hidro-energetic projects in Peru. In this article, the author analyzes the current regulation on water resources to then identify and analyze three inconsistencies between what is regulated, what is stated and what actually happens regarding the concept of turbined water, the concept of environmental flow, and the implementation of the Water Availability Leveraging Plan.